Combining Internet‐Based and Postal Survey Methods in a Survey among Gynecologists: Results of a Randomized Trial. (19th February 2017) - Ernst, Sinja Alexandra; Brand, Tilman; Lhachimi, Stefan K.; Zeeb, Hajo
Abstract : Objective: To assess whether a combination of Internet‐based and postal survey methods (mixed‐mode) compared to postal‐only survey methods (postal‐only) leads to improved response rates in a physician survey, and to compare the cost implications of the different recruitment strategies. Data Sources/Study Setting: All primary care gynecologists in Bremen and Lower Saxony, Germany, were invited to participate in a cross‐sectional survey from January to July 2014. Study Design: The sample was divided into two strata (A; B) depending on availability of an email address. Within each stratum, potential participants were randomly assigned to mixed‐mode or postal‐only group. Principal Findings: In Stratum A, the mixed‐mode group had a lower response rate compared to the postal‐only group (12.5 vs. 20.2 percent; RR = 0.61, 95 percent CI: 0.44–0.87). In stratum B, no significant differences were found (15.6 vs. 16.2 percent; RR = 0.95, 95 percent CI: 0.62–1.44). Total costs (in €) per valid questionnaire returned (Stratum A: 399.72 vs. 248.85; Stratum B: 496.37 vs. 455.15) and per percentage point of response (Stratum A: 1, 379.02 vs. 861.02; Stratum B 1, 116.82 vs. 1, 024.09) were higher, whereas variable costs were lower in mixed‐mode compared to the respective postal‐only groups (Stratum A cost ratio: 0.47, Stratum B cost ratio: 0.71). Conclusions: In this study, primary care gynecologists were more likely to participate by traditional postal‐only than by mixed‐mode survey methods that first offered an Internet option. However, the lower response rate for the mixed‐mode method may be partly due to the older age structure of the responding gynecologists. Variable costs per returned questionnaire were substantially lower in mixed‐mode groups and indicate the potential for cost savings if the sample population is sufficiently large.